Nutrient Characteristics and Fermented Rice Straw Degradation by Lignolitic TLiD and BopR Inoculums - Prihartini, I; Soebarinoto, Soebarinoto; Chuzaemi, S; Winugroho, M (ANIMAL PRODUCTION, 2009)
The research has been conducted to evaluate the nutritionâs characteristic and degradation of rice straw fermented Â with lignolitic inokulum in different incubation time.Â  Rice straw fermentation with lignolitik isolates increase the dry matter and crude protein content compare with dried fermented rice straw. On the other hand, fermentation decrease organic matter, crude fiber, and cellulose contents. The decreasing of OM, CF, and cellulose were lower than lignin. The fermentation with lignolitik inoculum increase the value of DM and OM degradation of rice straw in parameterÂ  non-soluble water fraction but degradable potentially(b), potensial of degradation (a+b) dan degradation time (c) BK dan BO but non significant to parameter water soluble fractions (a).Â  Fermentation with lignolitik inoculum increase the nutritive value and degradation rice strwa and the best treatment was combination of Â TLiD danÂ  BOpR inoculums in three days incubation. (Animal Production 11(1): 1-7 (2009)Â Key Words: rice straw, rice straw fermented, lignolitik, lignin biodegradation, nutrition